2005
DOI: 10.1093/rheumatology/keh538
|View full text |Cite
|
Sign up to set email alerts
|

Effects of once-weekly oral alendronate on bone in children on glucocorticoid treatment

Abstract: Once-weekly oral alendronate is well tolerated, suppresses bone resorption and may improve volumetric bone density at the lumbar spine and mechanical strength of the femoral shaft in children with chronic illness taking glucocorticoids. It does not affect bone growth. Larger controlled studies are needed to determine if these changes translate into reduced fracture incidence or greater peak bone mass. This study highlights the importance of differentiating between changes in bone size and changes in volumetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
112
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(116 citation statements)
references
References 28 publications
0
112
0
4
Order By: Relevance
“…Recent studies in children with OI have demonstrated increased BMD and reduced fracture risk using oral risedronate (116) and olpadronate (117). Oral alendronate increased BMD in children with moderate to severe OI, but no change in fracture risk was identified (118). At this point in time, oral BP use is reserved for patients with milder forms of OI without VF (i.e., risedronate is ineffective in reducing VF) (116) and in those who are particularly needle phobic or refuse IV BP treatment.…”
Section: Bp Therapymentioning
confidence: 96%
“…Recent studies in children with OI have demonstrated increased BMD and reduced fracture risk using oral risedronate (116) and olpadronate (117). Oral alendronate increased BMD in children with moderate to severe OI, but no change in fracture risk was identified (118). At this point in time, oral BP use is reserved for patients with milder forms of OI without VF (i.e., risedronate is ineffective in reducing VF) (116) and in those who are particularly needle phobic or refuse IV BP treatment.…”
Section: Bp Therapymentioning
confidence: 96%
“…123,[125][126][127] Pilot studies have also been conducted in adolescents with anorexia nervosa. 128 In osteogenesis imperfecta, an openlabel study examining the use of cyclic administration of intravenous pamidronate reported reduced pain and fractures associated with dramatic increases in BMD.…”
Section: Bisphosphonatesmentioning
confidence: 99%
“…Em crianças, a experiência com o alendronato e outros bisfosfonatos é muito limitada, e seu uso é reservado para pacientes com osteoporose idiopática juvenil, osteoporose induzida por glicocorticóides, osteogênese imperfeita, FOP, calcificação arterial infantil e displasia fibrosa (23)(24)(25) . O diltiazen, um bloqueador do canal de cálcio, inibe o influxo de cálcio para as células, o crescimento e a proliferação do tecido muscular liso dos vasos e dos fibroblastos.…”
Section: Discussionunclassified